Pemberdayaan Uang dalam Zakat Fitrah Perspektif Madzhab Hanafi dan Syafi’i - Wahyu Abdul Jafar (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2015)
This study was conducted to determine how the legal empowerment of money in tithes whether allowed or prohibited in perspective Hanafi and Shafi'i schools. This study is very important to accommodate the fact that occur in the community-related issues in the use of money to pay tithes. Modern society is now assumed that the use of the money easier and more practical so that they are many who pay tithes using money from the use of rice or other staple foods. From these studies it is known that the Shafi'i schools use money as a tithe is not allowed. Paying tithes should be the staple food, should not be issued in the form of zakat fitrah qimah or money worth. Meanwhile, according to Hanafis use of money in tithes permitted as long as the money is worth the staple food which is used as a tithe. But the important thing to note here, for those who bertaqlid on Hanafi when issuing tithes monetary amount should be within the limit of tithes according to Abu Hanifah.